2006
DOI: 10.1016/j.bcp.2005.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Berberine suppresses MEK/ERK-dependent Egr-1 signaling pathway and inhibits vascular smooth muscle cell regrowth after in vitro mechanical injury

Abstract: Vascular smooth muscle cell (SMC) proliferation plays an important role in the pathogenesis of atherosclerosis and post-angioplasty restenosis. Berberine is a well-known component of the Chinese herb medicine Huanglian (Coptis chinensis), and is capable of inhibiting SMC contraction and proliferation, yet the exact mechanism is unknown. We therefore investigated the effect of berberine on SMC growth after mechanic injury in vitro. DNA synthesis and cell proliferation assay were performed to show that berberine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…However, berberine has also been reported to have a lipid lowering effect by stabilizing hepatic LDL receptor mRNA in an ERK-dependent manner rather than promoting transcriptional activity [Abidi et al, 2005]. Moreover, it is also reported that berberine suppresses MEK/ERK-dependent signaling pathway to inhibit vascular smooth muscle cell regrowth [Liang et al, 2006]. Here, we find that berberine represses the phosphorylation of ERK signal induced by LPS and IFN-g. We also observed that an inhibitory effect of berberine on ERK Fig.…”
mentioning
confidence: 69%
“…However, berberine has also been reported to have a lipid lowering effect by stabilizing hepatic LDL receptor mRNA in an ERK-dependent manner rather than promoting transcriptional activity [Abidi et al, 2005]. Moreover, it is also reported that berberine suppresses MEK/ERK-dependent signaling pathway to inhibit vascular smooth muscle cell regrowth [Liang et al, 2006]. Here, we find that berberine represses the phosphorylation of ERK signal induced by LPS and IFN-g. We also observed that an inhibitory effect of berberine on ERK Fig.…”
mentioning
confidence: 69%
“…ANG II has been shown to activate multiple signaling pathways (74,84). Importantly, phosphorylation of mitogen-activated protein kinases (MAPKs) has been implicated in the contractile, mitogenic, and trophic responses of arterial VSMCs (16,42,44,47,67,86). Therefore, to determine whether RGS5 expression regulates ANG Fig.…”
Section: Rgs5 Expression Regulates the Functional Response In Vsmcsmentioning
confidence: 99%
“…Berberine could improve quality of life and decrease ventricular premature complexes and mortality in patients with chronic congestive heart failure [16]. Berberine has potential in the prevention of atherosclerosis and restenosis [17,18]. Berberine can block transient outward potassium current ( IA ) and delayed rectifier potassium current ( IK ) in a concentration-dependent manner in acutely isolated CA1 pyramidal neurons of rat hippocampus [19].…”
Section: Introductionmentioning
confidence: 99%